2018
DOI: 10.3389/fmicb.2018.01603
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Similarity and Preference for Specific Sites in Healthy Oral Cavity and Esophagus

Abstract: Human microbial communities are highly complex ecosystems, but it remains unclear if microbial compositions have any similarity in distinct sites of the oral cavity and esophagus in particular. Clinical samples were collected from three niches (saliva, tongue dorsum and supragingival plaque) of the oral cavity and three segments (upper, middle, and lower) of the esophagus in 27 healthy individuals. Bacterial V3-V4 region of 16S rRNA gene in these samples was amplified and sequenced on Illumina sequencing platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 52 publications
(63 reference statements)
10
50
4
Order By: Relevance
“…The colon has the largest microbiota in the body[20], whereas the esophagus has far fewer microbes. Although bacterial communities have been observed with high inter- and intra-individual variations, an overlapping community has been identified between sites[27,28]. Previous studies[20,29-31] have suggested that Firmicutes ( Clostridium , Ruminococcus , Eubacterium , Peptostreptococcus , Peptococcus , Lactobacillus-L ), Bacteroidetes , Proteobacteria ( Enterobacteriaceae ) and Actinobacteria ( Bifidobacterium-BF ) phyla constitute the majority of the human gut microbiota.…”
Section: Esophageal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The colon has the largest microbiota in the body[20], whereas the esophagus has far fewer microbes. Although bacterial communities have been observed with high inter- and intra-individual variations, an overlapping community has been identified between sites[27,28]. Previous studies[20,29-31] have suggested that Firmicutes ( Clostridium , Ruminococcus , Eubacterium , Peptostreptococcus , Peptococcus , Lactobacillus-L ), Bacteroidetes , Proteobacteria ( Enterobacteriaceae ) and Actinobacteria ( Bifidobacterium-BF ) phyla constitute the majority of the human gut microbiota.…”
Section: Esophageal Microbiotamentioning
confidence: 99%
“…The composition of the microbiota located in the normal esophagus is relatively conserved, and the estimated resident microbes are mainly composed of more than 100 species, most of which have already been identified[32,33]. The dominant microbes that colonize the normal esophagus are Streptococcus [32,33], and Dong L et al[28] reported that no distinct microbial preference exists in the upper, middle and lower esophagus. However, the microbiota varies in different esophageal diseases compared to the healthy esophagus[34].…”
Section: Esophageal Microbiotamentioning
confidence: 99%
“…Li [28] and their colleagues found that the normal esophagus ora is similar to the oral cavity ora. Firmicutes is the most abundant phyla, and no speci c ora exists in different parts of the esophagus.…”
Section: Discussionmentioning
confidence: 98%
“…Neisseria spp. are among the most abundant taxa in the oral cavity [39]. A predominance of Neisseria spp.…”
Section: Discussionmentioning
confidence: 99%